2012
DOI: 10.1021/jp210732u
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Dependent Reversible Assembly Properties of Polyvalent DNA–Silver Nanocube Conjugates

Abstract: We have synthesized polyvalent DNA–silver nanocube conjugates and investigated their chemical and physical properties. The DNA loading of the conjugates has been effectively controlled via chemical modification of the cube surface. Importantly, we have discovered that the reversible cooperative assembly properties of the conjugates are significantly associated with the flat surface of the conjugates’ cubic structure, which is distinctive from the conventional DNA–spherical nanoparticle conjugates. A DNA detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…17 Park et al observed the shape-dependent reversible binding affinity and self-assembly nature of Ag nanocube and DNA conjugates. 18 Tunable optoelectronic properties of plasmonic Au and Ag nanoparticles have been utilized as a superior sensing platform to detect DNA. Most of the groups reported fluorophore dye tagged DNA and used fluorescence probe to detect double and single stranded DNAs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17 Park et al observed the shape-dependent reversible binding affinity and self-assembly nature of Ag nanocube and DNA conjugates. 18 Tunable optoelectronic properties of plasmonic Au and Ag nanoparticles have been utilized as a superior sensing platform to detect DNA. Most of the groups reported fluorophore dye tagged DNA and used fluorescence probe to detect double and single stranded DNAs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The coupling of RCA and NEANA provides high sensitivity and great detection capacity for random target sequences by utilizing a fixed set of linker and particle probes and an easily modifiable padlock probe. Furthermore, we expect that this work can be extended for multiplexed colorimetric DNA detection with other types of nanoparticle systems displaying various colors 9g, 18. Applications of the methodology include rapid screening of specific DNA sequences and genotyping of single nucleotide polymorphisms.…”
Section: Methodsmentioning
confidence: 96%
“…Membrane protein studies [50], Photoluminescence [51], ultrasensitive biosensors [52], field enhancement [53] lithium ion batteries [54], solar cell application [55], photoresponsive liquid crystals [56] Drug delivery [57], nitrite sensing Nanocube molecular binding on membrane surfaces [58], Polyvalent DNA-Silver Nanocube Conjugates [59] increased-sensitivity localized surface plasmon resonance sensors revealed [60], electrocatalysts [61] Formic Acid Oxidation [62], methanol and ethanol electrooxidation [63] Dendritic nanostructure electrochemical DNA biosensor [64] Temperature-Sensitive Shell [65], flexible dye-sensitized solar cells [66] oxygen reduction [67], replacement reaction [68] Nanochain chemical vapor deposition [69], superior photocatalytic activity [70] surface-enhanced Raman scattering [71], water treatment [72], energy storage [73],…”
Section: Nanodiskmentioning
confidence: 99%